Witnessing farm animal abuse during work experience. Issue 7 (13th July 2017) - Brown, Richard
Abstract : THIS series gives readers the opportunity to consider and contribute to discussion of some of the ethical dilemmas that can arise in veterinary practice. Each month, a case scenario is presented, followed by discussion of some of the issues involved. In addition, a possible way forward is suggested; however, there is rarely a cut‐and‐dried answer in such cases, and readers may wish to suggest an alternative approach. This month's dilemma, 'Witnessing farm animal abuse during work experience', was submitted and is discussed by Richard Brown. Readers with comments to contribute are invited to send them as soon as possible, so that they can be considered for publication in the next issue. The series is being coordinated by Steven McCulloch, a practising vet with a PhD in the ethics of veterinary policy. It aims to provide a framework that will help practitioners find solutions when facing similar dilemmas.